2021
DOI: 10.1007/s11845-021-02679-z
|View full text |Cite
|
Sign up to set email alerts
|

A retrospective cohort study of risk factors and outcomes in older patients admitted to an inner-city geriatric unit in London during first peak of COVID-19 pandemic

Abstract: Purpose Compared to younger patients, coronavirus disease 2019 (COVID-19) clinical presentation in older people can be more heterogeneous and fatal. We aim to describe a cohort of older adults admitted in an inner-city London hospital during the first peak of the pandemic. Methods A retrospective observational study that enrolled older adults consecutively admitted into two geriatric wards with suspected or confirmed severe acute respiratory syndrome coronavirus 2 (SARS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
2
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
(31 reference statements)
0
7
2
1
Order By: Relevance
“…In this study, Hispanic or Latino/a/x individuals were less likely to be significantly associated with having a dysphagia diagnosis versus non-Hispanic/Latino/a/x individuals per instrumental swallow study. This finding is inconsistent with current research that suggests that consequences of COVID-19 infections differ by ethnicity, with greater rates of COVID-19 infection and death in Black, Hispanic, and Asian populations [ 29 31 ]. Disparities in healthcare access, preexisting comorbidities, inability to limit exposure due to housing arrangements or occupations may influence COVID-19 outcomes between ethnic groups [ 29 , 31 ].…”
Section: Discussioncontrasting
confidence: 86%
“…In this study, Hispanic or Latino/a/x individuals were less likely to be significantly associated with having a dysphagia diagnosis versus non-Hispanic/Latino/a/x individuals per instrumental swallow study. This finding is inconsistent with current research that suggests that consequences of COVID-19 infections differ by ethnicity, with greater rates of COVID-19 infection and death in Black, Hispanic, and Asian populations [ 29 31 ]. Disparities in healthcare access, preexisting comorbidities, inability to limit exposure due to housing arrangements or occupations may influence COVID-19 outcomes between ethnic groups [ 29 , 31 ].…”
Section: Discussioncontrasting
confidence: 86%
“…Over half of the studies included older adults (age ≥65 years), and 50.1% (13,187/26,303) of patients were female. Six frailty assessment tools were used, including the Clinical Frailty Score (CFS) (n=16) (7)(8)(9)11,(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), the Hospital Frailty Risk Score (HFRS) (n=1) (26), the Geriatric Nutritional Risk Index (GRNI) (n=1) (27), the modified Frailty Index (mFI) (n=1) (28), the Multidimensional Prognostic Index (MPI) (n=1) (29), and the Frail Non-Disabled Survey (FIND) (n=1) (10). The prevalence of frailty ranged from 9.1-87.2%, with a summary estimate rate of 51.4% (95% CI: 39.9-62.9%; I 2 =99.49%; Figure 2).…”
Section: Study Characteristicsmentioning
confidence: 99%
“…All of the included studies in this review that recorded mortality and frailty in COVID-19 patients identified older age and frailty as the leading causes of mortality. Increasing age was found as an independent risk factor for critical illness and higher mortality in COVID-19 patients [33,43]. Our results indicated that a significant difference was recorded (p < 0.001) according to age differences between frail and non-frail COVID 19 patients.…”
Section: Discussionmentioning
confidence: 47%
“…The percentage of older adults with frailty ranged from 21% [64] to 76.6% [33] of the total participants in each study.…”
Section: Sarcopenia and Frailty Measurementsmentioning
confidence: 99%
See 1 more Smart Citation